New Cysteine Protease Inhibitors: Electrophilic (Het)arenes and Unexpected Prodrug Identification for the Trypanosoma Protease Rhodesain - Klein, Philipp (Molecules, 2020)
Electrophilic (het)arenes can undergo reactions with nucleophiles yielding π- or Meisenheimer (σ-) complexes or the products of the S(N)Ar addition/elimination reactions. Such building blocks have only rarely been employed for the design of enzyme inhibitors. Herein, we demonstrate the combination of a peptidic recognition sequence with such electrophilic (het)arenes to generate highly active inhibitors of disease-relevant proteases. We further elucidate an unexpected mode of action for the trypanosomal protease rhodesain using NMR spectroscopy and mass spectrometry, enzyme kinetics and various types of simulations. After hydrolysis of an ester function in the recognition sequence of a weakly active prodrug inhibitor, the liberated carboxylic acid represents a highly potent inhibitor of rhodesain (K(i) = 4.0 nM). The simulations indicate that, after the cleavage of the ester, the carboxylic acid leaves the active site and re-binds to the enzyme in an orientation that allows the formation of a very stable π-complex between the catalytic dyad (Cys-25/His-162) of rhodesain and the electrophilic aromatic moiety. The reversible inhibition mode results because the S(N)Ar reaction, which is found in an alkaline solvent containing a low molecular weight thiol, is hindered within the enzyme due to the presence of the positively charged imidazolium ring of His-162. Comparisons between measured and calculated NMR shifts support this interpretation.